1977
DOI: 10.1177/00220345770560110901
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary Tooth Formation in Mouse Molar Transplants

Abstract: The dentition of mice and rats, which normally consists of one incisor and three molars per quadrant, is not generally known for the occurrence of an excess number of teeth. This report describes experimentally induced supernumerary teeth which were observed in 5 of 44 mouse molar explants.Second molar tooth germs and the adjacent third molar rudiment were dissected as one explant from the mandibles of 18-day C57BL/10 mouse embryos. Care was taken to exclude incisor tissue The explants were cultured for 2 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Jae‐Young Kim found that APCDD1 modulates the gene expression of Wnt‐ and EK‐related signalling molecules at the cap stage of tooth development and is involved in tooth cusp patterning by modulating the epithelial rearrangement . Supernumerary tooth formation in mouse molar transplants . During the development of mouse tooth germ, we found that APC expression levels gradually declined at the embryonic phase (E13.5, E14.5, E16.5 and E18.5).…”
Section: Discussionmentioning
confidence: 72%
“…Jae‐Young Kim found that APCDD1 modulates the gene expression of Wnt‐ and EK‐related signalling molecules at the cap stage of tooth development and is involved in tooth cusp patterning by modulating the epithelial rearrangement . Supernumerary tooth formation in mouse molar transplants . During the development of mouse tooth germ, we found that APC expression levels gradually declined at the embryonic phase (E13.5, E14.5, E16.5 and E18.5).…”
Section: Discussionmentioning
confidence: 72%
“…En otras anomalías como la disostosis cleidocraneal se ha reportado presencia de múltiples supernumerarios en 35% de los casos; y en pacientes con síndrome de Gardner en 21% de los afectados. (1,2,8,18,19) En unos pocos casos de pacientes con periodontitis juvenil localizada se ha informado la presencia de múltiples dientes supernumerarios y se ha sugerido la asociación entre estos desordenes (15) Estudios histológicos en ratas han demostrado que epitelio proliferativo remanente en áreas interseptales de la vaina radicular epitelial de Hertwig puede transformarse en células diferenciadas con posterioridad a trauma la cual da lugar a dientes supernumerarios (21) La presencia de dientes supernumerarios puede acarrear diversas irregularidades especialmente en la dentición mixta; en algunos casos pueden impedir la erupción de dientes permanentes o favorecer una erupción ectópica; en otros casos pueden desarrollar quistes; en cualquier caso una evaluación detallada clínica y radiológica debe preceder la conducta que se deba seguir (4,5)…”
Section: Introductionunclassified